PENGARUH KECENDERUNGAN BURNOUT TERHADAP KINERJA PETUGAS OPERATOR COMMAND CENTER 112 KOTA SURABAYA - Dwi Hardiningtyas; Awang Dhanny S (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2022)
Burnout is a state of emotional and physical fatigue, low productivity, and feelings of isolation, often caused by work-related stress. People who experience burnout / burnout at a high level are mostly inclined to withdraw from their work so that the results of the work done are not optimal and have an impact on performance. The research method used in this research is Exploratory Research using a Quantitative approach, the focus of this study is to determine the Effect of Burnout with Performance. The sampling technique in this study used a Purposive sampling technique with a sample size of 71 respondents. After testing the validity and reliability. Then the data obtained were analyzed using simple linear regression. This study found a strong and significant negative effect between Burnout and employee performance at the Surabaya Command Center 112 Surabaya. This is proven by the t value of (-15.268) while the t table is 1.99495 with Sig 0.000 at a Significant level of 5%. This study also found a coefficient of determination of 0.878. This means that the Burnout variable contribution is 87.8% on performance, while 12.2% are not examined in this study.